Honos alit artes. Studi per il settantesimo compleanno di Mario Ascheri. IV. L'età moderna e contemporanea Giuristi e istituzioni tra Europa e America - MAFFEI, PAOLA; Varanini, Gian Maria (Reti Medievali E-Book, 2014)
The studies included in this volume analyze the legal and social history of Europe and North America by the end of the eighteenth century to the contemporary age. The study investigates the relationship between culture and legal status (science, law and government), the administration of justice and the transformation of the legal professions. That lights up the separation, in the whole complex of Western legal tradition, that identifies the countries of the common law.